Francisella novicida Cas9 interrogates genomic DNA with very high specificity and can be used for mammalian genome editing - Acharya, Sundaram; Mishra, Arpit; Paul, Deepanjan; Ansari, Asgar Hussain; Azhar, Mohd; Kumar, Manoj; Rauthan, Riya; Sharma, Namrata; Aich, Meghali; Sinha, Dipanjali; Sharma, Saumya; Jain, Shivani; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Genome editing using the CRISPR/Cas9 system has been used to make precise heritable changes in the DNA of organisms. Although the widely used Streptococcus pyogenes Cas9 (SpCas9) and its engineered variants have been efficiently harnessed for numerous gene-editing applications across different platforms, concerns remain regarding their putative off-targeting at multiple loci across the genome. Here we report that Francisella novicida Cas9 (FnCas9) shows a very high specificity of binding to its intended targets and negligible binding to off-target loci. The specificity is determined by its minimal binding affinity with DNA when mismatches to the target single-guide RNA (sgRNA) are present in the sgRNA:DNA heteroduplex. FnCas9 produces staggered cleavage, higher homology-directed repair rates, and very low nonspecific genome editing compared to SpCas9. We demonstrate FnCas9-mediated correction of the sickle cell mutation in patient-derived induced pluripotent stem cells and propose that it can be used for precise therapeutic genome editing for a wide variety of genetic disorders.
Keywords: CRISPR Cas9; gene therapy; Genome editing; iPSCs; sickle cell anemia

Terminal uridylyl transferase mediated site-directed access to clickable chromatin employing CRISPR-dCas9 - George, Jerrin Thomas; Azhar, Mohd; Aich, Meghali; Sinha, Dipanjali; Ambi, Uddhav B.; Maiti, Souvik; Chakraborty, Debojyoti; Srivatsan, Seergazhi G. (Journal of the American Chemical Society, 2020)
Locus-specific interrogation of target genes employing functional probes such as proteins and small molecules is paramount in decoding the molecular basis of gene function and designing tools to modulate its downstream effects. In this context, CRISPR-based gene editing and targeting technologies have proved tremendously useful, as they can be programmed to target any gene of interest by simply changing the sequence of the single guide RNA (sgRNA). Although these technologies are widely utilized in recruiting genetically encoded functional proteins, display of small molecules using CRISPR system is not well developed due to the lack of adequate techniques. Here, we have devised an innovative technology called sgRNA-Click (sgR-CLK) that harnesses the power of bioorthogonal click chemistry for remodeling guide RNA to display synthetic molecules on target genes. sgR-CLK employs a novel posttranscriptional chemoenzymatic labeling platform wherein a terminal uridylyl transferase (TUTase) was repurposed to generate clickable sgRNA of choice by site-specific tailoring of multiple azide-modified nucleotide analogues at the 3' end. The presence of a minimally invasive azide handle assured that the sgRNAs are indeed functional. Notably, an azide-tailed sgRNA targeting the telomeric repeat served as a Trojan horse on the CRISPR-dCas9 system to guide synthetic tags (biotin) site-specifically on chromatin employing copper-catalyzed or strain-promoted click reactions. Taken together, sgR-CLK presents a significant advancement on the utility of bioorthogonal chemistry, TUTase, and the CRISPR toolbox, which could offer a simplified solution for site-directed display of small molecule probes and diagnostic tools on target genes.

FnCas9-based CRISPR diagnostic for rapid and accurate detection of major SARS-CoV-2 variants on a paper strip - Kumar, Manoj; Gulati, Sneha; Ansari, Asgar H.; Phutela, Rhythm; Acharya, Sundaram; Azhar, Mohd; Murthy, Jayaram; Kathpalia, Poorti; Kanakan, Akshay; Maurya, Ranjeet; Vasudevan, Janani Srinivasa; Aparna, S.; et al. (eLife, 2021)
The COVID-19 pandemic originating in the Wuhan province of China in late 2019 has impacted global health, causing increased mortality among elderly patients and individuals with comorbid conditions. During the passage of the virus through affected populations, it has undergone mutations, some of which have recently been linked with increased viral load and prognostic complexities. Several of these variants are point mutations that are difficult to diagnose using the gold standard quantitative real-time PCR (qRT-PCR) method and necessitates widespread sequencing which is expensive, has long turn-around times, and requires high viral load for calling mutations accurately. Here, we repurpose the high specificity of Francisella novicida Cas9 (FnCas9) to identify mismatches in the target for developing a lateral flow assay that can be successfully adapted for the simultaneous detection of SARS-CoV-2 infection as well as for detecting point mutations in the sequence of the virus obtained from patient samples. We report the detection of the S gene mutation N501Y (present across multiple variant lineages of SARS-CoV-2) within an hour using lateral flow paper strip chemistry. The results were corroborated using deep sequencing on multiple wild-type (n = 37) and mutant (n = 22) virus infected patient samples with a sensitivity of 87% and specificity of 97%. The design principle can be rapidly adapted for other mutations (as shown also for E484K and T716I) highlighting the advantages of quick optimization and roll-out of CRISPR diagnostics (CRISPRDx) for disease surveillance even beyond COVID-19. This study was funded by Council for Scientific and Industrial Research, India.

Rapid and accurate nucleobase detection using FnCas9 and its application in COVID-19 diagnosis - Azhar, Mohd; Phutela, Rhythm; Kumar, Manoj; Ansari, Asgar Hussain; Rauthan, Riya; Gulati, Sneha; Sharma, Namrata; Sinha, Dipanjali; Sharma, Saumya; Singh, Sunaina; Acharya, Sundaram; Sarkar, Sajal; et al. (Biosensors & Bioelectronics, 2021)
Rapid detection of DNA/RNA pathogenic sequences or variants through point-of-care diagnostics is valuable for accelerated clinical prognosis, as witnessed during the recent COVID-19 outbreak. Traditional methods relying on qPCR or sequencing are tough to implement with limited resources, necessitating the development of accurate and robust alternative strategies. Here, we report FnCas9 Editor Linked Uniform Detection Assay (FELUDA) that utilizes a direct Cas9 based enzymatic readout for detecting nucleobase and nucleotide sequences without transcleavage of reporter molecules. We also demonstrate that FELUDA is 100% accurate in detecting single nucleotide variants (SNVs), including heterozygous carriers, and present a simple web-tool JATAYU to aid end-users. FELUDA is semi-quantitative, can adapt to multiple signal detection platforms, and deploy for versatile applications such as molecular diagnosis during infectious disease outbreaks like COVID-19. Employing a lateral flow readout, FELUDA shows 100% sensitivity and 97% specificity across all ranges of viral loads in clinical samples within 1hr. In combination with RT-RPA and a smartphone application True Outcome Predicted via Strip Evaluation (TOPSE), we present a prototype for FELUDA for CoV-2 detection closer to home.
Keywords: CRISPRDx; FELUDA; FnCas9; LFA; SARS-CoV2; SNV detection